Prevalência de cárie dentária em gestantes atendidas no Sistema Único de Saúde em município paulista - Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; |Santos, Karina Tonini dos; Queiroz, Ana Paula Dossi Guimarães e [UNESP]; |Garbin, Cléa Adas Saliba [UNESP]| (My University, 2011)
The purpose of this study was to evaluate the dental caries prevalence and the use and needs of dental prosthetic in pregnant women attending in the National Health System in northwestern city of São Paulo state. The sample involved women, between 3 and 9 months of gestation, who were taking prenatal care in Health Units. Those who consented (n = 119) were examined and interviewed by calibrated dentists. We used the DMF-T index and indicators of the use and needs of dental prosthetic. The average age of the pregnant women was 24.7 years, the majority brown (48.7%) with complete high school (60.5%). The average DMFT was 11.7 and 25.2% and 46.2% of them require upper and lower prosthesis, respectively. The oral health indices showed a high DMT-F and great need for dental prostheses. The results show the need for actions directed, with the aim of to improve the specialized attention to the health of mothers and their babies.

O objetivo deste estudo foi avaliar a prevalência de cárie dentária e uso e necessidade de prótese em gestantes atendidas no Sistema Único de Saúde em município do noroeste paulista. A amostra contou com mulheres, entre o 3º e 9º mês de gestação, cadastradas nas Unidades de Saúde. As que consentiram (n=119) foram examinadas e entrevistadas por cirurgiões-dentistas calibrados. Utilizou-se os índices CPO-D e de uso e necessidades protéticas. A idade média das gestantes foi de 24,7 anos, sendo a maioria parda (48,7%), com o ensino médio completo (60,5%). O CPO-D médio foi 11,7 e 25,2% necessitam de prótese superior e 46,2%, inferior. Os índices de saúde bucal apontam um elevado CPOD e necessidade de próteses bucais. Os resultados evidenciam a necessidade de ações dirigidas, com a finalidade de melhorar a atenção especializada à saúde das mães e seus bebês.
Dental caries prevalence in pregnant women attending in the national health system in city of São Paulo State
Keywords: Epidemiology; Oral health; Pregnancy; Epidemiologia; Saúde bucal; Gravidez